Intra‐Articular Injection of Autologous Adipose Tissue‐Derived Mesenchymal Stem Cells for the Treatment of Knee Osteoarthritis: A Phase IIb, Randomized, Placebo‐Controlled Clinical Trial - Lee, Woo‐Suk; Kim, Hwan Jin; Kim, Kang‐Il; Kim, Gi Beom; Jin, Wook (Stem cells translational medicine, 2019)
Mesenchymal stem cells (MSCs) have been the focus of an emerging treatment for osteoarthritis. However, few studies reported about outcomes of an intra‐articular injection of autologous adipose‐derived mesenchymal stem cells (AD‐MSCs). This study aimed to assess the efficacy and safety of a single intra‐articular injection of AD‐MSCs for patients with knee osteoarthritis. It was a prospective double‐blinded, randomized controlled, phase IIb clinical trial. AD‐MSCs were administered for 12 patients (MSC group), and the group was compared with 12 knees with injection of normal saline (control group) up to 6 months. All procedures were performed in the outpatient clinic. Primary outcome measure was the Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) score. Secondary outcome measure included various clinical and radiologic examination, and safety after injection. Change of cartilage defect after injection was evaluated using magnetic resonance imaging (MRI). Single injection of AD‐MSCs led to a significant improvement of the WOMAC score at 6 months. In the control group, there was no significant change in the WOMAC score at 6 months. No serious adverse events were observed in both groups during the follow‐up period. In MRI, there was no significant change of cartilage defect at 6 months in MSC group whereas the defect in the control group was increased. An intra‐articular injection of autologous AD‐MSCs provided satisfactory functional improvement and pain relief for patients with knee osteoarthritis in the outpatient setting, without causing adverse events at 6 months' follow‐up. Larger sample size and long‐term follow‐up are required. Stem Cells Translational Medicine 2019;8:504–511 Autologous adipose‐derived mesenchymal stem cells (AD‐MSCs) were administered for 12 patients, and the group was compared with 12 knees with injection of normal saline up to 6 months. The procedures were performed in an outpatient clinic. An intra‐articular injection of autologous AD‐MSCs provided satisfactory functional improvement and pain relief in patients with knee osteoarthritis without causing adverse events at 6 months' follow‐up.